2020
DOI: 10.3389/fchem.2020.603577
|View full text |Cite
|
Sign up to set email alerts
|

Poly (Glycerol Sebacate)-Based Bio-Artificial Multiporous Matrix for Bone Regeneration

Abstract: In recent years, bone repair biomaterials that combine cells and bioactive factors are superior to autologous and allogeneic bone implants. However, neither natural nor synthetic biomaterials can possess all desired qualities such as strength, porosity, and biological activity. In this study, we used poly (glycerol sebacate) (PGS), a synthetic material with great osteogenic potential that has attracted more attention in the field of tissue (such as bone tissue) regeneration owing to its good biocompatibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Liang et al. [ 13 ] showed that PGS loaded with the adhesive ligands RGD and VEGF mimetic peptide could serve as a potential bone‐mimicking scaffold by enhancing cell infiltration, vascularization, and subsequent bone regeneration processes. Zaky et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al. [ 13 ] showed that PGS loaded with the adhesive ligands RGD and VEGF mimetic peptide could serve as a potential bone‐mimicking scaffold by enhancing cell infiltration, vascularization, and subsequent bone regeneration processes. Zaky et al.…”
Section: Discussionmentioning
confidence: 99%
“…Zaky et al [12] reported the successful application of PGS bioscaffolds in repairing critical-sized ulna defects in rabbits. Liang et al [13] showed that PGS loaded with the adhesive ligands RGD and VEGF mimetic peptide could serve as a potential bone-mimicking scaffold by enhancing cell infiltration, vascularization, and subsequent bone regeneration processes. Zaky et al [14] confirmed that PGS contributed to bone regeneration by recruiting MSCs and enhancing the osteogenic differentiation of MSCs by transmitting mechanical stimulation to the MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature is raised to room temperature and hold again for several hours, completing the freeze‐drying procedure. [ 22,50,53,148,150 ]…”
Section: Fabrication Techniques For Pgs‐based Biomaterialsmentioning
confidence: 99%
“…The temperature is raised to room temperature and hold again for several hours, completing the freeze-drying procedure. [22,50,53,148,150] Frydrych et al [22] used a PGS/PLLA mixture to replicate native fatty tissue. Fatty tissue is a specialized connective soft tissue composed of adipocytes.…”
Section: Freeze-dryingmentioning
confidence: 99%
“…When the bone defect reaches a certain limit, it is di cult to complete the defect healing by its own repair ability. The autologous bone graft has good biocompatibility and bone-inducing ability, demonstrating the gold standard for bone defect healing [5]. However, autologous bone grating is limited by donor site morbidity, which will inevitably lead to extension of surgical time, increase of surgical sites and infection chance and aggravation of patient pain [6,7].…”
Section: Introductionmentioning
confidence: 99%